EVALUASI PELAKSANAAN PENILAIAN AUTENTIK KURIKULUM 2013; STUDI KASUS DI MADRASAH IBTIDAIYAH NEGERI TEMPEL SLEMAN YOGYAKARTA (Jurnal Pendidikan Madrasah, 2016)
This study aims to describe how the implementation of authentic assessment of curriculum 2013 at MIN Tempel, and inhibiting factors as well as supporting the implementation of authentic assessment of curriculum 2013. With descriptive qualitative research through observation and interviews found that the results of the implementation of authentic assessment of curriculum in 2013 at MIN Tempel yet fully using the instrument according to the procedure authentic assessment. Factors supporting the implementation of the curriculum in 2013 is an authentic assessment decision of the Directorate General of Islamic Education, the madrasas continue the implementation of the curriculum in 2013, while the inhibiting factor is the lack of teachers' understanding of authentic assessment processes and instruments used in authentic assessment.